Critical thinking and academic succes of English language students - Pušina, Amir (Array, 2019)
The goal of this study is to examine the relationship between critical thinking skills and academic achievement of English language learners in relation to different personal and environmental factors. In total, 117 female and 54 male (N=171) English language and literature students (age of M=20.99, SD=2.43) from four different universities in Bosnia and Herzegovina participated. Critical thinking skills and socio-demographic characteristics were examined by Ennis-Weir Critical Thinking Essay Test (EWCT) and Demographic Data Questionnaire. Nonparametric statistical procedures were used to test relations of critical thinking skills and academic achievement (GPA) clustering for gender, age, family education level, university affiliation and year of study. Analysis indicated only one significant relation between the socio-demographic variables, EWCT and GPA scores: very weak negative correlation between age and GPA (rs=-.160, p˂.05), with a small effect size, accounting for 2.56% common variance. A statistically significant positive moderate correlation (rs=.41, p<.001) with medium effect size (16.81% variance) between EWCT and GPA was found. Furthermore, difference between EWCT mean rank scores by GPA grade levels was a statistically significant: χ2(4)=35.751, p<.001. According to these results, critical thinking skills are important for students’ academic achievement. Forthcoming research needs more clarification of socio-demographic, environmental factors and critical thinking skills relationship